Daluwarsa Tindak Pidana Korupsi Melalui Sudut Pandang Teori Hukum : Optimalisasi Pengembalian Kerugian Keuangan Negara - Fina Rosalina (Universitas Merdeka Madiun, 2022)
The imposition of the expiration date on the criminal act of corruption is still debatable whether it can enforce. The Corruption Eradication Act does not specifically regulate the expiration period, causing legal uncertainty and creating dualism of views on the application of the expiration period, which in turn has the potential to cause state financial losses. This study aims to find the expired concept of corruption through the point of view of legal theory. The legal theory used is the theory of consequences (leer van het gevolg). The critical use of the theory of consequences (leer van het gevolg) serves to embody the theoretical concepts and factual conditions of eradicating corruption in Indonesia. This study uses a normative juridical method that is prescriptive. This research found that the term act (feit) in the provisions of Article 79 of the Criminal Code means fulfilling all elements of a criminal act. Where the criminal act of corruption in the Law on the Eradication of Criminal Acts of Corruption is a material offense, must carry out the expiration since the result of state financial losses appears on the surface. The characteristics of white-collar crime in corruption are appropriate for applying the theory of consequences (leer van het gevolg). The jurisprudence of the Supreme Court's decision which states that the crime of corruption is a multi-national crime strengthens the implementation of the UNCAC international instrument regarding the extension of the expiration period of the criminal act of corruption. This study Concludes That the provisions of Article 79 of the Criminal Code regarding expiration are not suitable to be applied in cases of corruption in Indonesia